The Family Check-Up Online: A Telehealth Model for Delivery of Parenting Skills to High-Risk Families With Opioid Use Histories - Stormshak, Elizabeth A.; Matulis, Jordan M.; Nash, Whitney; Cheng, Yijun (Frontiers in Psychology, 2021)
The Family Check-Up has been tested in more than 25 years of research, across multiple settings, and is an evidence-based program for reducing risk behavior, enhancing parenting skills, and preventing the onset of substance use. It is designed to motivate parents to engage in positive parenting practices and to change problematic parenting and has been tested across a variety of ages including early childhood and adolescence. It is highlighted in NIDA’s Principles of Substance Use Prevention for Early Childhood: A Research-Based Guide as one of only three effective selective prevention programs for substance abuse among families with young children. Recently, we developed an online version of the Family Check-Up that has now been adapted for early childhood and families with opioid use histories. The online platform and telehealth model allow for wide-scale dissemination, ease of training with community providers, and increased public health reach for families in remote, rural areas. This is particularly important when targeting families with opioid misuse and addiction because there are high rates of addiction in remote areas, yet few services available. In this article, we describe the Family Check-Up Online and review new content in the model that targets a population of young adult parents with substance abuse histories, including opioid use. New modules include content focused on harm reduction for this high-risk population of parents, such as safety in the home, substance use while parenting, and managing conflict with partners and friends. We describe our iterative process for developing this content and include data from focus groups and stakeholders who have provided feedback.